Students’ Perceptions of Socio-Scientific Issues in Biology Education: A Case Study in Indonesia - Ashidiq, Rizki Maulana; Amri, Muhammad Fahriza; Rahmat, Adi; Winarno, Nanang; Hamdiyati, Yanti (Universitas Islam Negeri Raden Intan Lampung, 2024)
Understanding students' perceptions of socio-scientific issues (SSI), particularly in the context of biology, is essential for developing effective teaching strategies. This study analyzes students’ perceptions of SSI in biology, involving 360 participants from 10th- and 11th-grade classes at a high school in Majalengka, West Java, Indonesia. The participants, aged 16 to 17 years, were equally divided between the two grade levels. Data were collected using a 24-item survey questionnaire based on a five-point Likert scale. The results show an overall mean perception score of 3.31, indicating that students generally hold a neutral perception of SSI in biology. A weak correlation was observed between students’ overall perceptions and SSI in biology, with a p-value of 0.08 and an r-value of 0.02. Further analysis revealed minor differences in perceptions based on grade level and gender, with 10th-grade students scoring an average of 3.30 and 11th-grade students scoring 3.32. Male students averaged 3.28, while female students averaged 3.34. These findings suggest that although students exhibit neutral perceptions of SSI in biology, many struggle to connect biological concepts to real-life contexts. This highlights the need for further research to identify factors influencing students’ perceptions and to explore alternative learning models for improving understanding and engagement with SSI in biology.